Oropharyngeal dysphagia is a prevalent risk factor for malnutrition in a cohort of older patients admitted with an acute disease to a general hospital. Issue 3 (June 2015) - Carrión, Silvia; Cabré, Mateu; Monteis, Rosa; Roca, Maria; Palomera, Elisabet; Serra-Prat, Mateu; Rofes, Laia; Clavé, Pere
Summary Background & aims Oropharyngeal dysphagia and malnutrition are prevalent conditions in the older. The aim of this study was to explore the relationship between oropharyngeal dysphagia, nutritional status and clinical outcome in older patients admitted to an acute geriatric unit. Methods We studied 1662 patients ≥70 years consecutively hospitalized with acute diseases, in whom dysphagia could be clinically assessed by the volume-viscosity swallow test and nutritional status with the Mini Nutritional Assessment®. Anthropometric and laboratory measurements were taken and mortality recorded during hospital stay, at 6 months and one year after discharge was recorded. Results 47.4% (95% CI 45–49.8%) patients presented oropharyngeal dysphagia and 30.6% (95% CI 27.9%–33.3%), malnutrition. Both conditions were associated with multimorbidity, multiple geriatric syndromes and poor functional capacity (p < 0.001). However, patients with dysphagia presented increased prevalence of malnutrition (MNA® < 17 45.3% vs 18%, p < 0.001) regardless of their functional status and comorbidities (OR 2.31 (1.70–3.14)) and lower albumin and cholesterol levels. Patients with malnutrition presented an increased prevalence of dysphagia (68.4% (95% CI 63.3–73.4)). Patients with dysphagia and patients with malnutrition presented increased intrahospital, 6-month and 1-year mortality rates (p < 0.05). The poorest outcome was for patients with both conditions (1-year mortality was 65.8%). Conclusions Prevalence of dysphagia was higher than malnutrition in our older patients. Dysphagia was an independent risk factor for malnutrition, and both conditions were related to poor outcome.